2013
DOI: 10.1186/1472-6920-13-123
|View full text |Cite
|
Sign up to set email alerts
|

Programmatic assessment of competency-based workplace learning: when theory meets practice

Abstract: BackgroundIn competency-based medical education emphasis has shifted towards outcomes, capabilities, and learner-centeredness. Together with a focus on sustained evidence of professional competence this calls for new methods of teaching and assessment. Recently, medical educators advocated the use of a holistic, programmatic approach towards assessment. Besides maximum facilitation of learning it should improve the validity and reliability of measurements and documentation of competence development. We explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
237
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(260 citation statements)
references
References 31 publications
(48 reference statements)
9
237
0
14
Order By: Relevance
“…In the context of the applied theoretical model of longitudinal programmatic assessment at the Faculty of Veterinary Medicine, Utrecht University, every individual assessment is low stakes/formative. However, earlier research showed that in the practical implementation of this theoretical framework, students do not seem to perceive individual assessments as formative, but rather as summative (Bok et al 2013b). The findings in this study might suggest that some students -the high performing ones -do see the beneficial effects of feedback in developing themselves and are more likely to use the feedback in a rather formative way.…”
Section: Discussionmentioning
confidence: 37%
“…In the context of the applied theoretical model of longitudinal programmatic assessment at the Faculty of Veterinary Medicine, Utrecht University, every individual assessment is low stakes/formative. However, earlier research showed that in the practical implementation of this theoretical framework, students do not seem to perceive individual assessments as formative, but rather as summative (Bok et al 2013b). The findings in this study might suggest that some students -the high performing ones -do see the beneficial effects of feedback in developing themselves and are more likely to use the feedback in a rather formative way.…”
Section: Discussionmentioning
confidence: 37%
“…A educação e o treinamento do estudante de Medicina compõem um programa formativo, sendo assim também pertinente conceber a avaliação do estudante como tendo uma dimensão programática. Deste modo, pode-se conceituar a avaliação programática como um conjunto de ações diversificadas, mas coordenadas, que se desenvolvem em diferentes momentos, compondo um verdadeiro programa, visando ao cumprimento, da melhor forma possível, das várias funções da avaliação do estudante [5][6][7][8][9][10][11] . Em outras palavras, pode-se entender a avaliação programática do estudante como uma forma inovadora de aplicar conceitos tradicionais, para que as funções da avaliação sejam cumpridas com eficácia (fitness-for-purpose).…”
Section: A Avaliação Do Estudanteunclassified
“…Uno de los instrumentos de evaluación más utilizado en la construcción del espacio común de educación superior en todas las ramas de conocimiento, y de forma más concreta en Ciencias de la Salud, es el portafolios (Saltman Tavabie y Kidd, 2012;Vaughan et al, 2012;Forte, de Souza, da Silva, do Prado y Rodrigues, 2013;Vance et al, 2013;Chiu Lee y Ho, 2014;Haldane, 2014), especialmente por su capacidad para evaluar las competencias desarrolladas por el estudiante (Suraseranivongse et al, 2011;Cheung, 2011;Atahawi et al, 2012;Webb et al, 2014) y por el protagonismo que otorga al alumnado en su proceso de aprendizaje y evaluación (Finlay, Probyn y Ho, 2012;Bok et al, 2013). No obstante, a pesar de las ventajas que conlleva su utilización, no está exento de dificultades (Driessen Van Tartwijk, Van Der Vleuten y Wass, 2007).…”
Section: Importancia Del Portafolios Para La Evaluación De Competenciasunclassified
“…La reforma universitaria europea defiende un modelo educativo "competencial" en el que las decisiones sobre el currículo (especialmente las relativas a los contenidos, la metodología y evaluación) se realizan en función de las competencias que los estudiantes deben demostrar al finalizar la titulación cursada (Biggs, 2004;Colás, Jiménez y Villaciervos, 2005;Martínez y Echeberría, 2009; Atahawi, Sisk, Poloskey, Hicks y Dannefer, 2012;Bok et al, 2013).…”
Section: Introductionunclassified